2005
DOI: 10.1094/pd-89-1109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seeding Rate and Seed Treatment Fungicides on Agronomic Performance, Fusarium Head Blight Symptoms, and DON Accumulation in Two Winter Wheats

Abstract: Fusarium head blight (FHB), caused by Fusarium graminearum, is an important disease of wheat (Triticum aestivum). FHB reduces yield and quality, and the pathogen produces several toxins in the grain, the most important being deoxynivalenol (DON). In North America, the foliar fungicide tebuconazole is used to reduce FHB symptoms and DON accumulation. Because of the narrow window required for its application, uniform flowering of wheat is important. The objective of this study was to investigate the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Some other studies have also reported negative effects of some fungicide seed treatments on crop performance. Schaafsma and Tamburic-Ilincic (2005) found that in the field Raxil 250 FL resulted in fewer plants and a lower density of tillers and spikes than other treatments, and was similar to the untreated infected control. Martin and Matters (2002) also reported that the Raxil-Thiram treatment had a lower yield than the untreated infected control, but that there was no difference in kernel weight among treatments.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Some other studies have also reported negative effects of some fungicide seed treatments on crop performance. Schaafsma and Tamburic-Ilincic (2005) found that in the field Raxil 250 FL resulted in fewer plants and a lower density of tillers and spikes than other treatments, and was similar to the untreated infected control. Martin and Matters (2002) also reported that the Raxil-Thiram treatment had a lower yield than the untreated infected control, but that there was no difference in kernel weight among treatments.…”
Section: Discussionmentioning
confidence: 56%
“…Although there have been previous controlled-environment and field studies on the effectiveness of fungicide seed treatments against Fusarium seed infection of cereal crops, results have not been consistent (Klein and Burgess 1987;Gilbert and Tekauz 1995;Schaafsma et al 2001;Schaafsma and Tamburic-Ilincic 2005). Furthermore, most of the studies on Fusarium-infected seed have concentrated on F. graminearum, whereas in the western prairies there are usually other Fusarium species and fungal species present in seed from FHB-affected wheat crops.…”
mentioning
confidence: 96%
“…Given the potential role of seed treatments, there have been relatively few studies on seed treatment and its impact on stand establishment, winter survival and crop yield, especially in western Canada. In Ontario, Schaafsma and Tamburic-Ilincic (2005) reported that a fungicide seed treatment increased fall seedling emergence and the number of tillers the following spring. Most products also increased yield in the presence of Fusarium head blight caused by Fusarium graminearum, but seed and soil-borne disease levels and causal agents were not assessed.…”
mentioning
confidence: 99%
“…Crop responses to seed treatments can extend beyond mitigation of pathogens or insect pests. Studies of winter wheat report improved plant stands, yield components, and grain yield where only a fungicide seed treatment such as tebuconazole was applied (Schaafsma and Tamburic-Ilincic, 2005). A Canadian study on canola reported improved seedling emergence and grain yield with dual fungicide/insecticide seed treatments (Hwang et al, 2015).…”
mentioning
confidence: 99%
“…to roots and coleoptiles of seedlings in a trial carried out under greenhouse conditions (Jørgensen et al 2012). Some fungicidal STs increased winter wheat plant stands and grain yield; however, the effectiveness of the same STs in managing FHB were inconsistent (Schaafsma and Tamburic-Ilincic 2005). May et al (2010) reported that fungicidal ST did not always improve seedling emergence and had no significant effect on grain yield.…”
Section: Introductionmentioning
confidence: 99%